Development of Conformable Substrates for OLEDs Using Highly Transparent Bacterial Cellulose Modified with Recycled Polystyrene. (3rd March 2021) - Cebrian, Ariane V. S.; Carvalho, Rafael S.; Barreto, Arthur R. J.; Maturi, Fernando E.; Barud, Hernane S.; Silva, Robson R.; Legnani, Cristiano; Cremona, Marco; Ribeiro, Sidney J. L.
Abstract: Bacterial cellulose (BC) is a biocompatible and nontoxic biopolymer that has been successfully used as a substrate for flexible organic light emitting diodes (OLEDs). Although BC membranes exhibit excellent mechanical properties and industrial scalability, they are semitransparent, which limits their performance. To improve the optical properties of BC membranes, methods such as the polymerization of different inorganic–organic hybrid materials and petrochemical derivative monomers have been considered; however, these methods require considerable time and effort. In this work, transparent BC membranes for conformable OLEDs substrates are fabricated by spray coating a solution of recycled petrochemical plastics, found in expanded foam package wastes, and d‐limonene, which is a green solvent extracted from orange peels. This fabrication approach is highly scalable and can be considered a sustainable technique to develop high performance transparent substrates for photonic applications based on both recovered petrochemical polymers and naturally occurring biopolymers. In terms of the morphological and structural properties, the resulting transparent membranes exhibit a lower roughness than pristine BC. The resulting BC‐PS composite is used as a substrate for OLED fabrication. The conformable OLEDs exhibit a current efficiency of up to 5 cd A −1 (16 000 cd m −2 ) and power density of ≈2.8 mW cm −2 . Abstract : The use of d‐limonene, which is a renewable green solvent, to recover polystyrene (PS) from waste material and increase the transparency and hydrophobicity of bacterial cellulose (BC) is considered to obtain a conformable substrate. Transparent BC‐PS membranes are obtained by using the low‐cost airbrush technique through a sustainable approach, being evaluated as conformable substrates for organic light emitting diode application.